Design and analysis of physical layer security aspects in MIMO-OFDM based WiMAX network - Bhattacharyya, Budhaditya; Deb, Ipsita; Sharma, Nalini (International Journal of Engineering and Technology, 2018)
The protocol 802.16 of the IEEE proposed a technology of wireless broadband called WiMAX which overcomes the limitations of other wireless technologies that came prior to WiMAX. WiMAX has acquired significant attention owing to its mobility support, longer trans-mission range and higher transmission rate. In order to ensure usability and reliability, a number of security concerns are required to be addressed in WiMAX. The first part of this work is to analyze the performance of a MIMO-OFDM based WiMAX under Rayleigh fading channel using SIMULINK environment under diverse encoding algorithms and adaptive modulation schemes in terms of throughput and bit-error-rates. The second objective being its performance analysis using various standard cryptographic algorithms such as Rivest-Shamir-Adleman (RSA), Data Encryption Standard (DES) and Advanced Encryption Standard (AES), which enhances the security and efficiency of a WiMAX networks. Â Â